(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the development of a scheme for predicting the psychomotor development of preschool children, which is of great importance for health authorities when organizing specialized pediatric and medical-pedagogical, preventive services. The proposed method allows early diagnosis and prevention of disorders of psychomotor development in preschool children, which is of important medical and social importance.